(3GdYde GdecJSH aj RQY GdPgHs - (3CHhGdbGSe eMeO Hf CMeO GdSeGhi GdYQGbj,J (B580 (3g` s
(3ChdgG (B:s
(3GeG HYO aMbjb Ydjce eYTQ GdeJThbjf Edi ZGjI GdfLGI Cf JJYQahG SHjdgG Ef cfJe UGObjf s
(3BNQgG (B:s
(3hCdgefG ac GdQehR GdJi JcJegG GdCee GdYGHQI MJi YQafG GdSQ ai fThFfG GdChd hdG JZJQf HgPg GdOfjG agj ZGOQI Je GdcJGH s
(3HgG NeS UhQ edhfI ZjQ eJbfIs
(3ai GdcjejGA GdcGPHIs
(3hajg PcQ eGgjI GdQehR hcjajI TQMgGs
(3hgj eQUYI HbUGFO GdLdjGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B81s
Keywords: (3GdcjejGA h GdWHjYjGJs